The influence of body fat content and distribution on bone mass in healthy Chinese adults - Chen, Bin; Liu, Gongwen; Wang, Yike; Xu, Youjia (Frontiers in Medicine, 2024)
Background: Previous studies have reported a close relationship between body mass index (BMI) and bone mineral density (BMD). However, the effects of fat on bone mass remain controversial, particularly for fat tissue distribution.This study was to evaluate the association between regional fat percentage and BMD using a population-based database.Methods: This study included participants who were referred to the Department of Radio diagnosis for dual-energy X-ray absorptiometry (DEXA) scan from January 2018 to December 2020. The relationships of BMI and regional fat percentage with BMD were assessed by multiple linear regression and generalized additive models. The risk of low bone mass was determined using logistic regression.Results: There was a negative relationship between the regional fat percentage and femoral neck BMD (FN BMD) or lumbar spine BMD (LS BMD) in both genders (P<0.05). In females, an inverted U-shaped relationship was observed between regional fat percentage and BMD at both femoral neck and lumbar spine. The impact of trunk fat percentage on LS BMD was associated with the highest OR of low bone mass in females (OR 3.1, 95% CI 2.6 to 3.7, p for trend <0.001), while the impact of abdomen fat percentage on FN BMD was associated with the highest OR of low bone mass in males (OR 2.2, 95% CI 1.8 to 2.7, p for trend <0.001).There was an inverted U-shaped relationship between regional fat percentage and BMD. Excessive regional fat percentage may be harmful to bone health in both genders. To promote bone health, males should restrict their abdomen circumference and avoid abdominal adiposity, while females should control their trunk circumference.